EFEKTIFITAS PEMAHAMAN KNOWLEDGE AND RAINBOW SKILL ABAD 21 TERHADAP PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS DIGITAL - MUKHLISAH, IFFAH; FAJRIN, RARA INTAN MUTIARA; PANGESTU , WISNU AJI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
This research aims to determine: (1) the understanding of Knowledge and Rainbow skills of the 21st century by KKGMI teachers in Sidoharjo District, Sragen Regency (2) the use of digital-based learning media by KKGMI teachers in Sidoharjo District, Sragen Regency (3) To what extent is the influence of understanding Knowledge and Rainbow skills in the 21st century on use of digital-based learning media by KKGMI teachers, Sidoharjo District, Sragen Regency. This research uses a Quantitative approach with a True Experimental Design research type. The research location was carried out at Madrasah Ibtidaiyah in Sidoharjo District, Sragen Regency and carried out for approximately 3 months from September to October 2023. The research population was MI teachers in the KKMI Sidoharjo Sragen area, totaling 110 teachers. The sampling technique is Simple Random sampling technique with a sample size of 40 teachers. The data collection instruments used were test instruments, questionnaires and documentation. The analysis technique uses unit analysis techniques and hypothesis testing is product moment. Before the data is analyzed, a normality test and homogeneity test are carried out, then a hypothesis test is carried out with the data with the help of the SPSS 26 application. The research results show that: (1) Understanding Knowledge and Rainbow the 21st century skills of KKGMI teachers in Sidoharjo District, Sragen Regency are in the medium category with the number of teachers being 22 people or 55%; (2) the use of digital-based learning media by KKGMI teachers in Sidoharjo District, Sragen Regency is in the medium category with the number of teachers being 27 people or 68%; (3) understanding of 21st century Knowledge and Rainbow skills regarding the use of digital-based learning media by KKGMI teachers in Sidoharjo District, Sragen Regency with a significance value of 0.035<0.050 and a Pearson product moment value of 0.334>0.05. There is a positive relationship so, it can be said that there is an influence between the two variables. ABSTRAKPenelitian ini bertujuan untuk mengetahui: (1) pemahaman Knowledge and Rainbow skill abad 21 guru KKGMI Kecamatan Sidoharjo Kabupaten Sragen (2) penggunaan media pembelajaran berbasis digital guru KKGMI Kecamatan Sidoharjo Kabupaten Sragen (3) Sejauh mana pengaruh pemahaman Knowledge and Rainbow skill abad 21 terhadap penggunaan media pembelajaran berbasis digital guru KKGMI Kecamatan Sidoharjo Kabupaten Sragen. Penelitian ini menggunakan jenis pendekatan Kuantitatif dengan jenis penelitian True Eksperimental Design. Tempat penelitian dilaksanakan di Madrasah Ibtidaiyah di Kecamatan Sidoharjo Kabupaten Sragen dan dilaksanakan selama Kurang lebih 3 bulan dari bulan dari bulan September sampai Okltober 2023. Populasi penelitian adalah para guru MI di wilayah KKMI Sidoharjo Sragen yang berjumlah 110 guru. Teknik pengambilan sampel adalah Teknik Simple Random sampling dengan jumlah sampel 40 guru. Instrumen pengumpulan data yang dipergunakan adalah menggunakan instrumen tes, angket dan dokumentasi. Teknik analisis menggunakan teknik analisis unit dan uji hipotesis adalah product moment, sebelum data dianalisis maka dilakukan uji normalitas dan uji homogenitas, baru dilakukan uji Hipotesis dengan data tersebut dengan bantuan aplikasi SPSS 26. Hasil Penelitian menunjukkan data bahwa: (1) pemahaman Knowledge and Rainbow skill abad 21 guru KKGMI Kecamatan Sidoharjo Kabupaten Sragen berada dalam kategori sedang dengan jumlah guru 22 orang atau 55%; (2) penggunaan media pembelajaran berbasis digital guru KKGMI Kecamatan Sidoharjo Kabupaten Sragen berada pada kategori sedang dengan jumlah guru 27 orang atau 68%; (3) pemahaman Knowledge and Rainbow skill abad 21 terhadap penggunaan media pembelajaran berbasis digital guru KKGMI Kecamatan Sidoharjo Kabupaten Sragen dengan nilai signifikasi 0,035<0,050 dan nilai Pearson product moment 0,334>0,05. Terdapat hubungan yang positif sehingga, bisa dikatakan ada pengaruh antar kedua variabel.